Bridging Digital Health and Sasak Tradition: A Narrative Inquiry into the BERIUK Program for Preconception Nutrition Education - Baiq Eka Putri Saudia; Imtihanatun Najahah; I Gusti Ayu Putu Sriwahyuni; Lely Cintari (International Journal of Educational Narratives, 2026)
Background. The nutritional status of maternal and child health is a determinant of the quality of human resources. This is increasingly clear with evidence that the nutritional status and health of mothers during preconception, pregnancy, and breastfeeding are very critical periods. The importance of preconception nutrition is closely related to the incidence of Stunting. NTB Province is one of the provinces that contributes to stunting of 77,037 toddlers. Therefore, prospective brides and grooms require adequate nutrition to ensure optimal preconception health and reduce the risk of stunting in their future children. Purpose. to find out the role of BERIUK (Berugaq Information Education) for Prospective Brides and Grooms in increasing knowledge and attitudes about pre-conception nutrition using the Android application media Gipsi (Pre-Conception Nutrition). Method. The study used a quasi-experimental with a pretest-posttest group approach. It was conducted in West Lombok Regency, NTB Province with 60 prospective brides and grooms. Data were analyze using paired t-tests to determine differences in knowledge and attitudes before and after the intervention.   Results. The results showed a significant increase in knowledge and attitudes after the intervention. The t-test revealed a significant difference in knowledge (p = 0.000 < ? = 0.05) and attitudes (p = 0.001 <?=0.05), indicating that education via BERIUK significantly improved both outcomes among prospective brides and grooms. Conclusion. Combining culturally relevant education with digital media is highly effective. Using BERUIK alongside the Gipsi Android application significantly increased knowledge and positively influenced attitudes regarding preconception nutrition among prospective brides and grooms.